THE INFRARED PROPERTIES OF SOURCES MATCHED IN THE WISE ALL-SKY AND HERSCHEL ATLAS SURVEYS - Bond, N; Benford, D; Gardner, J; Amblard, A; Fleuren, S; Blain, A; Dunne, L; Smith, D; Maddox, S; Hoyos, C; Baes, M; Bonfield, D; et al. (2012)
We describe the infrared properties of sources detected over 36deg 2 of sky in the GAMA 15 hr equatorial field, using data from both the Herschel Astrophysical Terahertz Large-Area Survey (H-ATLAS) and Wide-field Infrared Survey (WISE). With 5σ point-source depths of 34 and 0.048mJy at 250 μm and 3.4 μm, respectively, we are able to identify 50.6% of the H-ATLAS sources in the WISE survey, corresponding to a surface density of 630deg-2. Approximately two-thirds of these sources have measured spectroscopic or optical/near-IR photometric redshifts of z < 1. For sources with spectroscopic redshifts at z < 0.3, we find a linear correlation between the infrared luminosity at 3.4 μm and that at 250 μm, with ±50% scatter over 1.5 orders of magnitude in luminosity, 109-10 10.5 L. By contrast, the matched sources without previously measured redshifts (r ≳ 20.5) have 250-350 μm flux density ratios which suggest either high-redshift galaxies (z ≳ 1.5) or optically faint low-redshift galaxies with unusually low temperatures (T ≲ 20). Their small 3.4-250 μm flux ratios favor a high-redshift galaxy population, as only the most actively star-forming galaxies at low redshift (e.g., Arp 220) exhibit comparable flux density ratios. Furthermore, we find a relatively large active galactic nucleus fraction (30%) in a 12 μm flux-limited subsample of H-ATLAS sources, also consistent with there being a significant population of high-redshift sources in the no-redshift sample. © © 2012. The American Astronomical Society. All rights reserved.